Analisis Sistem Manajemen Pergudangan dan Perancangan Standard Operating Procedure (SOP) Pada PT. X - Noval Aryanto; Apid Hapid Maksum (Jurnal Ilmiah Wahana Pendidikan, 2022)
PT. X is a company engaged in leather tanning. This company has problems with the warehousing management system and procedures in carrying out work on the warehouse section. The purpose of this research is expected to be able to review the work in the warehouse and produce a decrease in costs at the warehouse, the collection and delivery of goods into the warehouse can be more effective and efficient. Based on the results of the analysis and discussion that has been carried out on improvements to the warehousing management system, it is found that suggestions for improvements in receiving activities, storage activities, shipping activities, and control activities have been carried out. Improvements to the layout of the storage of goods resulting from observations and interviews, using a fishbone diagram for the results obtained, it is necessary to continuously improve and procure SOPs for every activity in the warehouse. With the standard operating procedure (SOP) in every activity in the warehouse, workers have an obligation to comply with procedures or policies that have been made by the company. Standardization can be used as a measurement tool for employee performance.